2022
DOI: 10.1093/eurheartj/ehac706
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiplatelet therapy duration after percutaneous coronary intervention in high bleeding risk: a meta-analysis of randomized trials

Abstract: Aims The optimal duration of dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) in patients at high bleeding risk (HBR) is still debated. The current study, using the totality of existing evidence, evaluated the impact of an abbreviated DAPT regimen in HBR patients. Methods and results A systematic review and meta-analysis was performed to search randomized clinical trials comparing abbreviated [i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 48 publications
0
22
1
1
Order By: Relevance
“…These finding are in line with previous reports (4). Collectively, evidence from these studies support an intensified/prolonged antithrombotic regimen may be particularly useful in high-ischemic risk patients, particularly if not at high risk for bleeding (5).…”
Section: Editorial On the Research Topic Precision Medicine For Antit...mentioning
confidence: 84%
“…These finding are in line with previous reports (4). Collectively, evidence from these studies support an intensified/prolonged antithrombotic regimen may be particularly useful in high-ischemic risk patients, particularly if not at high risk for bleeding (5).…”
Section: Editorial On the Research Topic Precision Medicine For Antit...mentioning
confidence: 84%
“…17,18 We demonstrated here that the ischemic/bleeding trade-off remains nearly unchanged when HBR patients have concomitant PAD, a strong predictor of ischemic complications. Effective bleeding avoidance strategies for HBR patients undergoing PCI include early discontinuation of aspirin or P2Y 12 inhibitor [19][20][21][22] as well as dual antiplatelet therapy (DAPT) de-escalation from a potent P2Y 12 inhibitor to Clopidogrel. 23,24 Whether these strategies are safe and effective in PAD patients needs to be determined in dedicated studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings could be applicable in both populations; nevertheless, the theoretical benefit would be greater in those with high or very high bleeding risk. Montalto et al showed that abbreviated DAPT is beneficial in patients under oral anticoagulation, while Costa et al supported that a 1- or 3-month DAPT regimen was related with reduced bleedings and cardiovascular mortality, without increasing ischemic events [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%